2016
DOI: 10.1128/jcm.02479-15
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-HIV Strategy for Complete Genome Sequencing

Abstract: bMolecular surveillance is essential to monitor HIV diversity and track emerging strains. We have developed a universal library preparation method (HIV-SMART [i.e., switching mechanism at 5= end of RNA transcript]) for next-generation sequencing that harnesses the specificity of HIV-directed priming to enable full genome characterization of all HIV-1 groups (M, N, O, and P) and HIV-2. Broad application of the HIV-SMART approach was demonstrated using a panel of diverse cell-cultured virus isolates. HIV-1 non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…In contrast, O-Vpus generally failed to show significant activity against human tetherin. In this study, we confirmed that most HIV-1 O strains use Nef to counteract tetherin but also identified an exception and show that the Vpu protein of RBF206, an HIV-1 O strain isolated from a 47-year-old woman in France (37), is a potent antagonist of human tetherin. RBF206 Vpu and Nef both display anti-tetherin activity in transient-transfection assays and in the context of the HIV-1 M NL4-3 molecular clone.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In contrast, O-Vpus generally failed to show significant activity against human tetherin. In this study, we confirmed that most HIV-1 O strains use Nef to counteract tetherin but also identified an exception and show that the Vpu protein of RBF206, an HIV-1 O strain isolated from a 47-year-old woman in France (37), is a potent antagonist of human tetherin. RBF206 Vpu and Nef both display anti-tetherin activity in transient-transfection assays and in the context of the HIV-1 M NL4-3 molecular clone.…”
supporting
confidence: 74%
“…An infectious molecular clone was constructed using unique BstEII (nucleotide position 2121), DraIII (nucleotide position 4152), and NheI (nucleotide position 8067) restriction enzyme sites and inserted between the MluI and NotI restriction sites of the pSMART-topo vector. Notably, the sequence of this RBF206 clone differs from a second independently derived consensus sequence of the same isolate, which was generated after an additional PBMC passage (37), by four nucleotides; however, none of these changes fell within the vpu gene, which is identical between the two consensus sequences. The pSMART-topo vector is a derivative of pSMART-LC-Amp containing the multiple-cloning site of pCR-XL TOPO from MluI to NotI.…”
Section: Methodsmentioning
confidence: 91%
“…Complete genomes of HIV and co-infecting viruses can be obtained directly from patient specimens, provided viral loads are high enough (Luk et al, 2015 ; Yamaguchi et al, 2017 ). To increase sensitivity, the HIV-SMART method utilizes reverse primers in conserved sequences of HIV fused to a tag to facilitate combined virus-specific priming and amplification (Berg et al, 2016 ; Rodgers et al, 2017a ). In an alternate HIV-specific approach, individual long fragments (e.g., >2 kb) amplified with HIV primer pairs can be converted to NGS libraries to achieve detection limits nearing that of PCR, although the process is more labor intensive (Gall et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…of clinical variables to transmission clusters, it is ideal to characterize within patient viral variation as individual sequence variants (haplotypes) instead of combining all of the individual reads into a single consensus sequence 94,95 . Therefore, haplotypes for each patient were predicted from the sequence data using HAPHPIPE's haplotype stages.…”
Section: Haplotype Reconstruction For the Identification Of Transmismentioning
confidence: 99%